(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The man-land correlation is a mutually dependentobservable fact. Man directly depends on the plants, animals and mineralresources and utilizes these to fulfill his day-to-day needs. Man’s activitiesare controlled by ecological factors and he has to adjust to nature to someextent. Forests, grasslands, marshes, plain cultivable land, hilly terrain,mountain slopes, wooded areas, river valleys, sand, etc. are the varied rangeof land categories that are available for him and its available products intheir natural or wild form and the outcome of the activities (cultivation,terracing) carried out by him in these land categories provide him sustenance.The existing studies focus on one kind of environment mainly the Ganga Valleythat has been the focus of study by historians and several gaps exist in thestudy of the so called ’peripheral’ regions.